Building Industrialization and Prefabrication between Materiality and Immateriality - Sergio Russo Ermolli; Giuliano Galluccio (Agathón)
This paper aims to investigate the possibilities offered by the design and production paradigms of Industry 4.0 in the Architecture, Engineering & Construction industry, through the coordination between systems for the integrated management of the design process (Building Information Modeling) and rapid prototyping tools (Computer-Aided Manufacturing). Is hereby proposed an interpretation of the meaning that an industrial transformation of the AEC industry takes over for the Architectural design, simulating a methodology in a BIM environment for the design of residential buildings in Cold-Formed Steel with drywall envelopes, exploiting the potential of digital manufacturing and computational design advanced tools.